2016
DOI: 10.1002/slct.201600576
|View full text |Cite
|
Sign up to set email alerts
|

Role of Unmodified Low Generation - PAMAM Dendrimers in Efficient Non-Toxic Gene Transfection

Abstract: The present study is focused on a simple execution in the applicability of non-toxic lower generation poly amidoamine (PA-MAM) dendrimers as effective nano-vectors in targeted gene delivery to the skin. So far the first three lower generation (G1, G2 and G3) PAMAM dendrimers have been overlooked as nucleic acid therapeutics. In this study, we have first carried out a systematic biophysical analysis to analyze their ability for plasmid DNA (pDNA) condensation and subsequent release by ethidium bromide assay to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The internalization of Rho-PAM, assessed by the intense red fluorescence inside the cells (Fig. 6A ), validate the use of this PAMAM derivative as a novel non-toxic delivery vector 31 , 32 .…”
Section: Discussionmentioning
confidence: 54%
“…The internalization of Rho-PAM, assessed by the intense red fluorescence inside the cells (Fig. 6A ), validate the use of this PAMAM derivative as a novel non-toxic delivery vector 31 , 32 .…”
Section: Discussionmentioning
confidence: 54%
“…Our studies focused only on the use of low-generation PAMAM dendrimers, i.e., generation 0.0 and 1.0 (having 4 and 8 free NH 2 , respectively), since it has been shown that they avoid the steric hindrance and toxicity issues which are characteristic of higher generations [28,38,39]. In particular, the non-toxicity of the auxiliary is of importance for leather processing (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of dendriplexes relies on gel electrophoresis, zeta potential determination, , atomic force microscopy (AFM), , dynamic light scattering (DLS), ,, isothermal titration calorimetry (ITC), ,, and circular dichroism (CD). ,,, Although these analytical methods are efficient to attest to the existence of the supramolecular nucleic acid/dendrimer complexes, they cannot afford a structural description of the dendriplexes at the molecular level. Molecular Dynamics (MD) investigations have recently been introduced for dendriplex structural description. , For instance, Maiti et al used MD simulations in explicit solvent to investigate the structures of dendriplexes associating PAMAM G2–4 to a 38-base ss-DNA and PAMAM G3–5 to a 38-base ds-DNA …”
Section: Introductionmentioning
confidence: 99%